Artificiality in the Delegation of Authority of Regional Heads and Their Impact on Autonomous Development - Susilo, Tri Achmad Budi; Fernandez, Frederik; Lestari, Ratna Ani; Boli, Agustinus Payong; Pakage, Ferdinant (Universitas Kristen Cipta Wacana, 2024)
The purpose of this study is to analyze the implications for the development of autonomous regions caused by the apparent delegation of authority from the regional head to the regional apparatus. The approach method used in this research is a descriptive-analytical approach. The practice of taking power in a covert manner, namely taking over the authority that has been delegated by the Regional Head to the Regional Apparatus without revoking the laws and regulations which are the legal basis for the delegation of authority, based on Law Number 23 of 2014 concerning Regional Government (as amended by Law No. 2 of 2015 concerning regional government). The covert takeover of authority from the Regent of East Flores from the Regional Secretary of East Flores as the Coordinator of Regional Financial Management and Head of the Regional Budget and Revenue Management Team, clearly has implications for the development process of the autonomous region. In a public policy that is not pro-people, it also has consequences for the progress of regional development and becomes a barrier to the realization of welfare for the people in the region